Mucins in Intestinal Mucosal Defense and Inflammation: Learning From Clinical and Experimental Studies - Grondin, Jensine A.; Kwon, Yun Han; Far, Parsa Mehraban; Haq, Sabah; Khan, Waliul I. (Frontiers in Immunology, 2020)
Throughout the gastrointestinal (GI) tract, a distinct mucus layer composed of highly glycosylated proteins called mucins plays essential roles in providing lubrication for the passage of food, participating in cell signaling pathways and protecting the host epithelium from commensal microorganisms and invading pathogens, as well as toxins and other environmental irritants. These mucins can be broadly classified into either secreted gel-forming mucins, those that provide the structural backbone for the mucus barrier, or transmembrane mucins, those that form the glycocalyx layer covering the underlying epithelial cells. Goblet cells dispersed among the intestinal epithelial cells are chiefly responsible for the synthesis and secretion of mucins within the gut and are heavily influenced by interactions with the immune system. Evidence from both clinical and animal studies have indicated that several GI conditions, including inflammatory bowel disease (IBD), colorectal cancer, and numerous enteric infections are accompanied by considerable changes in mucin quality and quantity. These changes include, but are not limited to, impaired goblet cell function, synthesis dysregulation and altered post-translational modifications. The current review aims to highlight the structural and functional features as well as the production and immunological regulation of mucins and the impact these key elements have within the context of barrier function and host defense in intestinal inflammation.